Imatinib for the Treatment of Pulmonary Arterial Hypertension and Pulmonary Capillary Hemangiomatosis. (1st June 2014) - Nayyar, Dhruv; Muthiah, Kavitha; Kumarasinghe, Gayathri; Hettiarachchi, Ravin; Celermajer, David; Kotlyar, Eugene; Keogh, Anne
Abstract : Despite currently available treatments, the prognoses of pulmonary arterial hypertension (PAH) and pulmonary capillary hemangiomatosis (PCH) remain poor. Platelet‐derived growth factor and its receptor (PDGFR) have been implicated in the pathogenesis of pulmonary hypertension in PAH and PCH. Imatinib, a PDGFR antagonist, may be beneficial in the treatment of both conditions because of its potent antiproliferative effect. We report two cases that demonstrate the potential for safe and efficacious use of imatinib in PAH and PCH.